Anesthesia secrets (Mosby/Elsevier, 2006)
One thousand plus questions and answers provide a knowledge base in anesthesia and offer insights on the decisive and safe practice of anesthesia. The 78 chapters review the basics of patient management, pharmacology, preparing for anesthesia, patient monitoring, perioperative problems, systemic diseases, and anesthetic considerations for selected surgical procedures. The fourth edition decreases the number of chapters by 11, removing the entire section on critical care.